Persistence of Granuloma or granulomatous Inflammation after Six Months of CAT-1 Anti Tuberculosis Therapy in Tubercular Lymphadenitis Patients (Bangladesh Journal of Medical Science, 2023)
Background: Tuberculous Lymphadenitis is the most common form of extra-pulmonary tuberculosis. Paradoxical enlargement and new lymph nodes appearance are observed after completion of anti-tuberculous therapy.Objective: The objective of the study was to assess whether granuloma can persist in persisted or paradoxically enlarged lymph node after anti-TB treatment in tubercular lymphadenitis patient.Method: An observational cross sectional study was conducted in the Department of Internal Medicine, Bangabandhu Sheikh Mujib Medical University from March 2014 to February 2016 among patients of TB-lymphadenitis who had persistent or enlargement of previous or developed new lymph node after anti-TB therapy. History was taken; previous records were analyzed to ascertain the diagnostic basis of tuberculosis. History and physical examination were done for present status. Cytological or histopathological analysis was done at Department of Pathology, BSMMU.Result: Most of the patients were in the 21-30 years age group (Mean 25.53±7.93). Majority of them were female. Most of the respondents were student. More than half of the patients came from lower socioeconomic status. About 89% had typical symptoms of tuberculosis like fever, weight loss and loss of appetite during initial diagnosis and about one third had typical symptom of TB like fever weight loss and loss of appetite and one third had no symptoms after treatment. Majority mode of diagnostic tool was FNAC in both initial and after treatment. Majority (88.9 %) cases granuloma persisted after treatment.Conclusion: In spite of anti TB treatment with good compliance granuloma or granulomatous inflammation persisted in majority patients of persisted lymph nodes.Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 216-221